Carbon Materials as Positive Electrodes in Bromine‐Based Flow Batteries. Issue 1 (13th January 2022) - Popat, Yaksh; Trudgeon, David; Zhang, Caiping; Walsh, Frank C.; Connor, Peter; Li, Xiaohong
Abstract: Bromine based redox flow batteries (RFBs) can provide sustainable energy storage due to the abundance of bromine. Such devices pair Br2 /Br − at the positive electrode with complementary redox couples at the negative electrode. Due to the highly corrosive nature of bromine, electrode materials need to be corrosion resistant and durable. The positive electrode requires good electrochemical activity and reversibility for the Br2 /Br − couple. Carbon materials enjoy the advantages of low cost, excellent electrical conductivity, chemical resistance, wide operational potential ranges, modifiable surface properties, and high surface area. Here carbon based materials for bromine electrodes are reviewed, with a focus on application in zinc‐bromine, hydrogen‐bromine, and polysulphide‐bromine RFB systems, aiming to provide an overview of carbon materials to be used for design and development of bromine electrodes with improved performance. Aspects deserving further R&D are highlighted. Abstract : Carbon materials demonstrate suitable physical and chemical properties for applications in bromine based redox flow batteries (RFBs). This review summarizes the bromine/bromide reaction mechanisms taking place at the carbon electrode and provides an overview of different carbon based materials as the bromine electrodes. Built on this, its application in three RFB systems (e. g. zinc‐bromine, hydrogen‐bromine, and polysulphide‐bromine) have been examined in detail. A perspective highlights the importance of surface activation and treatment and aspects deserving further R&D.